MASLAHAH REVIEW OF THE DOWRY (MARRIAGE COST) BUGIS-MAKASSAR COMMUNITY - Sudirman Sudirman; Sabri Samin; Hasyim Aidid; Abd. Halim Talli Talli (Jurnal Ilmiah Al-Syir'ah, 2019)
The study examines the review of maslahah of uang panaik (bride price) in Bugis Makassar community. This study method used a descriptive qualitative approach that describes the phenomenon in Bugis Makassar's society. The results of the study indicated that uang panaik is a custom or ‘urf in Bugis Makassar community that is implemented at every wedding reception. Previous Islamic jurists have built and developed the Maslahah theory which concludes that all rules in Islam were benefit-oriented. There were three levels of maslahah theory, namely maslahah daruriyyah, maslahah hajiyyah, and maslahah tahsiniyah. Uang panaik was more inclined to maslahah hajjiyyah because it was a necessity in every marriage in Bugis Makassar community.